Pengentasan Orang Miskin di Indonesia: Peran Modal Sosial yang Terlupakan - Yamin, Sofyan; Dartanto, Teguh (UI Scholars Hub, 2016)
The government has a dominance role and heavily focused on economic approach in poverty alleviaton in Indonesia. Poverty rate has been reduced, but not in significant way. Revitalization of poverty alleviation programs by promoting non-economic such as social capital becomes important. This study aims to analyze the role of social capital related to the bonding and bridging dimension in promoting poverty alleviation and protecting the poor from vulnerability. Based on the study, the bonding and bridging dimension has showed the significant effect to decrease the vulnerability and pulled out the poor from the poverty line.